2020
DOI: 10.5811/westjem.2020.7.47405
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Elderly and Very Elderly Emergency Patients with Sepsis: A Retrospective Study

Abstract: Introduction: Elderly patients are at increased risk of developing sepsis and its adverse outcomes. Diagnosing and prognosing sepsis is particularly challenging in older patients, especially early at emergency department (ED) arrival. We aimed to study and compare the characteristics of elderly and very elderly ED patients with sepsis and determine baseline factors associated with in-hospital mortality. We also compared prognostic accuracy of the criteria for systemic inflammatory response syndrome, quick sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 27 publications
3
50
1
3
Order By: Relevance
“…Therefore, we suggest that lower BT in older sepsis patients is associated with a worse prognosis. Our results are supported by those of previous studies, which showed that hypothermia is a significant predictor of mortality in sepsis patients older than 65 years 25 , 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we suggest that lower BT in older sepsis patients is associated with a worse prognosis. Our results are supported by those of previous studies, which showed that hypothermia is a significant predictor of mortality in sepsis patients older than 65 years 25 , 26 .…”
Section: Discussionsupporting
confidence: 92%
“…The current study demonstrated the different predictive performance of the qSOFA score for in-hospital mortality between young and elderly OAPN patients; the qSOFA score predicted in-hospital mortality with high accuracy in young patients (AUC, 0.85), whereas its prognostic accuracy was modest in elderly patients (AUC, 0.61). This trend was also observed in several previous studies, in which the AUC of the qSOFA score was less than 0.70 in elderly patients [ 17 , 18 , 19 ]. The sensitivity and specificity of qSOFA score ≥ 2 for in-hospital mortality were 80% and 80% in young patients, and 50% and 68% in elderly patients, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Given that age is an independent predictor of do not resuscitate (DNR) status, 16 elderly patients may have a higher rate of DNR status 16 and, thus, a higher mortality rate and lower likelihood of undergoing invasive procedures (e.g, intubation). 17 Finally, at the time of this study, certain medications were experimental drugs that adhered to strict inclusion criteria. Elderly patients with more comorbidities may have been more likely to have been excluded in the clinical trials because of underlying conditions.…”
Section: Discussionmentioning
confidence: 99%